Haemorrhagic shock due to spontaneous splenic haemorrhage complicating antiplatelet therapy: endovascular management - Garge S Shaileshkumar; Keshava N Shyamkumar; Ahmed Munawwar; Purushothaman Vijayan; Perakath Benjamin (SpringerOpen, 2015)
Spontaneous splenic haemorrahge and rupture is a rare but life-threatening condition requiring urgent diagnosis and treatment. Splenic haemorrhage and rupture precipitated by thrombolytic or antiocoagulant therapy has been reported frequently in the literature, but only two cases due to ticlopidine and one case due to salicyclate have been reported. We report the case of a 54-year-old man with haemorrhagic shock due to spontaneous splenic haemorrhage and rupture following dual antiplatelet (aspirin and clopidogrel) therapy. He was successfully treated with selective angioembolization of the bleeding branch of the splenic artery.